Strategies for Targeting SARS CoV-2: Small Molecule Inhibitors—The Current Status - Beeraka, Narasimha M.; Sadhu, Surya P.; Madhunapantula, SubbaRao V.; Rao Pragada, Rajeswara; Svistunov, Andrey A.; Nikolenko, Vladimir N.; Mikhaleva, Liudmila M.; Aliev, Gjumrakch (Frontiers in Immunology, 2020)
SARS-CoV-2-induced COVID-19 cases have been increasing at an alarming rate (~7.4 million positive cases as on 11th June 2020), causing a high mortality (~4,17,956 deaths as on 11th June 2020) and economic loss (~3.2% shrink in global economy in 2020) across 212 countries globally. The clinical manifestations of this disease are pneumonia, lung injury, inflammation, and severe acute respiratory syndrome (SARS). Currently, there is no vaccine or effective pharmacological agent(s) available for the prevention/treatment of SARS-CoV2 infections. Moreover, development of a suitable vaccine is a challenging task due to antibody-dependent enhancement (ADE) and Th-2 immunopathology, which aggravates infection with SARS-CoV-2. Furthermore, the emerging SARS CoV-2 strain exhibits several distinct genomic and structural patterns compared to other coronavirus strains, hence, making a suitable vaccine development even more difficult. Therefore, the identification of novel small molecules inhibitors (NSMIs) that can interfere with viral entry or viral propagation is of special interest and is the need-of-the hour to manage already infected cases. SARS-CoV-2 infection is mediated by the binding of viral Spike protein (S-protein) to human cells through a 2-step process, which involves Angiotensin Converting Enzyme-2 (ACE2) and Transmembrane Serine Protease (TMPRSS)-2. Therefore, development of novel inhibitors of ACE2 / TMPRSS2 is likely to be beneficial to combat SARS-CoV-2 infections. However, the usage of ACE-2 inhibitors to block the SARS-CoV-2 viral entry requires additional studies as there are conflicting findings and severe health complications reported in patients. Hence, the current interest is shifted towards the development of NSMIs, which includes natural antiviral phytochemicals and Nrf-2 activators to manage SARS-CoV-2 infection. It is imperative to investigate the efficacy of existing antiviral phytochemicals, Nrf-2 activators to mitigate the SARS-CoV-2-mediated oxidative stress. Therefore, in this review, we have reviewed structural features of SARS-CoV-2 with special emphasis on key molecular targets and their known modulators that can be considered for the development of NSMIs.